Development of Academic Information System to Improve School Service Quality at SMK Negeri 1 Pundong - Puspita, Astrid; Eka Putri, Dhea (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This study aims to develop a desktop-based Academic Information System (AIS) and analyze its effect on improving school service quality at SMK Negeri 1 Pundong through integrated management of teacher data, student data, employee data, inventory, correspondence, and schedules.Methodology: The study employed Research and Development (R&D) method with waterfall model (needs analysis, design, coding, testing). The system was developed using Borland Delphi 7 programming language and Microsoft Access database. Data were collected through unstructured interviews and needs analysis questionnaires distributed to 86 teachers and staff, as well as black box testing and performance testing by experts and users.Main Findings: Expert testing results obtained a score of 83.75% (very good) and user testing obtained 86.81% (very good). Service Quality-based functionality testing achieved 86.33% with the highest dimension on Tangibles (89.33%). The system successfully integrated eight main menus and proved to increase service speed (95%) and ease of operation (91.25%).Novelty/Originality of this study: The novelty of this research lies in the development of a comprehensive AIS that integrates eight school management functions into one integrated platform, as well as evaluating its impact on service quality through active user participation since the needs analysis stage, differing from previous studies that only focused on single functions such as grade management or student admission.